(3QSGdI aj GdJYQjHs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd eHfi cdGe GdYQH Ydi GdeHfi hGdeYQH hHYO agPg QSGdI eQJHI ai JMbjb JYQjH GdcdeI GdCYLejI hJaUjd CbSGeg hPdc Cf GdYQH ceG JSJYed GdcdeI GdCYLejI s
(3BNQgG (B:s
(3cPdc JJeg GdQSGdI ceG Cf GdYQH YQHJ HYV dZGJ GdeYLe , cPdc GdYLe YLe HYV dZGJ GdYQH hefg HGRjGQ hgh eUdM HGZ RjGQ ai dZI GdYLe HeYfi GdeUdM , hefg TgQjGQ JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B192 - (3U(B208s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B152) s
Keywords: (3GddZIs